• Упростить выражения:
    1. [tex] x-y-\frac{x^2+y^2}{x-y}
    [/tex]
    2. [tex] \frac{a^2+b^2}{a+b}-a-b
    [/tex]

Ответы 1

  • 1) x -y -(x^2 +y^2)/(x-y) == [(x-y)^2 -x^2 -y^2]/(x-y) = (x^2 -2xy +y^2 -x^2 -y^2)/(x-y) = -2xy/(x-y) = 2xy/(y-x)2) (a^2 +b^2)/(a+b) -a -b == [a^2 +b^2 -(a+b)^2]/(a+b) = (a^2 +b^2 -a^2 -2ab -b^2)/(a+b) = -2ab/(a+b)
    • Автор:

      oscar28
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years